How does Transnational Labour Migration Shape Food Security and Food Sovereignty? Evidence from Nepal - Sunam, R.; Adhikari, Jagannath (Routledge, 2016)
Achieving food security has become a critical development issue. It is more so for Nepal, a country facing serious social and economic problems. In recent years, Nepal has seen rising temporary-work migration of people to foreign countries with implications for food security, even in distant rural places. In this article, we examine differential effects of transnational labour migration on food security and food sovereignty in migrant-sending rural areas. In so doing, we draw on the fresh insights gained from case studies carried out in villages representing two distinct geographical regions of Nepal – Tarai (Plains) and Hills. Findings show complex and contradictory effects of transnational labour migration. We argue that this form of migration has led to improved food security on a short-term basis through remittances and migration-induced rural employment. At the same time, it has also caused erosion in food sovereignty through generating adverse effects on local food production, and thus creating growing dependence on food imports and threatening poor people's access to food. Rather than considering food security and food sovereignty as rival frameworks, this paper suggests that combining the two concepts offer rich and broader understandings of the impacts of migration on rural people’s access to food.